USING THREE PHASE TECHNIQUE WITH VOCABULARY QUIZ AS A PRE ACTIVITY TO IMPROVE STUDENTS’ READING PERFORMANCE - Amroji Amroji (JURNAL ILMIAH BAHASA DAN SASTRA, 2021)
The objective of the study is to find out how to use three phase technique with vocabulary quiz as a pre activity to improve students’ reading performance, specifically, their reading motivation and comprehension achievement. This was a classroom action research and there were two cycles in this study. The result displayed the procedures of using three phase technique with vocabulary quiz as a pre activity was effective to improve students’ reading performance. The procedures, which covers four main phases: the vocabulary quiz, the pre, whilst and post reading activities, had fulfilled the criteria of success in this study. This fact was clearly shown by the increase of students’ reading motivation as indicated by their learning orientation in reading class. They were at least externally imposed to the rules that they accepted as norms to follow so as not to feel guilty. Their attitudes and behaviors toward reading class were good enough as expected by the teacher. The students’ reading comprehension achievement was also improved to 66.73 as their average score of reading comprehension test had gained the minimal passing grade expected by the school curriculum that was 65. Furthermore, it is possible that the procedures of this reasearch can get better result for the future study if they are applied more deliberately and more effectively.